2011
DOI: 10.1186/1756-0500-4-45
|View full text |Cite
|
Sign up to set email alerts
|

Managing chronic hepatitis B: A qualitative study exploring the perspectives of people living with chronic hepatitis B in Australia

Abstract: BackgroundThe implementation of a comprehensive public health response to hepatitis B in Australia is urgently required to reduce the increasing burden of hepatitis B infection on the health system and the community. A significant gap in the public health response to hepatitis B is an understanding of how people with chronic hepatitis B (CHB) respond to CHB.FindingsA qualitative study involving semi-structured interviews and focus group discussions was conducted. Interviews were held with 20 people with CHB fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
88
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(98 citation statements)
references
References 11 publications
9
88
0
1
Order By: Relevance
“…While previous studies have reported knowledge gaps among Australian people with CHB, [10][11][12] this current study is the largest Australian study quantifying hepatitis B knowledge and identifying some of the factors associated with hepatitis B knowledge in this population. Consistent with research from North America 15,16 and Asian countries, 17,18 the current study found that people with CHB had inadequate knowledge of hepatitis B.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While previous studies have reported knowledge gaps among Australian people with CHB, [10][11][12] this current study is the largest Australian study quantifying hepatitis B knowledge and identifying some of the factors associated with hepatitis B knowledge in this population. Consistent with research from North America 15,16 and Asian countries, 17,18 the current study found that people with CHB had inadequate knowledge of hepatitis B.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Data describing how people with CHB in Australia understand their infection is limited. While two studies report knowledge gaps among people with CHB, 10,11 only one singlecentre study quantitatively evaluated health literacy in this population. 12 This current study sought to assess the hepatitis B knowledge and associated factors among a group of Australian people with CHB from different healthcare centres.…”
mentioning
confidence: 99%
“…An interview topic guide (informed by the literature) was developed to explore views of the current practice of testing, barriers to testing, interactions with other services, and training and guidelines for HCV testing. [24][25][26][27][28][29][30][31][32][33][34] With written informed consent, interviews were audio-recorded and anonymised transcripts (transcribed by the interviewer) were imported into NVivo (version 9) to aid data analysis. Thematic analyses identified issues of particular salience for participants and across the dataset.…”
Section: Qualitativementioning
confidence: 99%
“…Other hepatitis B-related fears and concerns have also been reported among people with CHB in several other studies (3, 5, 10, 13, 17-19, 21-23) with these psychological stressors possible predisposing factors to developing psychiatric disorders, particularly depressive disorders. In one study among people with CHB, having hepatitis B-related concerns were associated with the presence of major depression (3).…”
Section: Discussionmentioning
confidence: 57%
“…Only one qualitative study interviewing 20 people with CHB reported a significant fear of the future or of dying among several participants (13). …”
Section: Introductionmentioning
confidence: 99%